Perubahan Orientasi Seksual pada Remaja Gay di Kabupaten Sukabumi - Rexi Junjunan Illahi; Mirna Nur Alia Abdullah; Wilo Dati (Ideas Publishing, 2022)
This study focused on adolescents who have a gay sexual orientation. The theory in this research is symbolic interactionism according to George Harbert Mead. The method used in this research is a qualitative approach with a case study method to obtain results and data analysis. Data collection techniques used are observation, interviews, and documentation. In determining the research informants, the researcher used a non-probability sampling technique, namely purposive sampling based on several predetermined criteria. The results of this study found several factors that influence changes in sexual orientation, namely hormonal and genetic factors, environmental factors, parenting factors, economic factors, social media factors, and trauma factors.